The impact of an integrated intervention program combining drug therapy with water, sanitation, and hygiene (WASH) education on reinfection with intestinal parasitic infections among the Karen hill tribe in northern Thailand - Woottichai Nachaiwieng; Sangob Sanit; Nattharinee Kongta; Jassada Saingamsook; Suwit Duangmano; Sakorn Pornprasert; Pradya Somboon; Jintana Yanola (Parasites & Vectors)
Abstract Background Intestinal parasitic infections (IPIs) are a major health problem among the Karen hill tribe in Thailand. This study aimed to evaluate the effect of an integrated intervention program of drug therapy combined with water, sanitation, and hygiene (WASH) education on reinfection with IPIs among the Karen hill tribe in an endemic area of northern Thailand. Methods A quasi-experimental study was conducted in two Karen villages, involving 691 residents, in Omkoi District, Chiang Mai Province; one village was designated as the intervention group and the other as the control group. Baseline information was collected regarding the infections and participants’ knowledge, attitudes, and practices (KAP) related to prevention and control of IPIs. Detection of benzimidazole resistance linked to the beta-tubulin gene mutation in soil-transmitted helminths (STH) was performed using polymerase chain reaction (PCR) amplification and DNA sequencing. Mass drug administration (MDA) with albendazole was applied to both groups. The intervention group received WASH education, whereas the control group did not. Follow-up assessments were conducted at 3 and 6 months. Results Baseline data revealed a 36.0% (123/342) prevalence of IPIs in the intervention group and 36.8% (96/261) in the control group. The most common helminth and pathogenic protozoan were Trichuris trichiura and Giardia lamblia, respectively. No non-synonymous mutations in the beta-tubulin gene were found. Post-intervention at 3-month and 6-month follow-ups revealed that the prevalence of IPIs in the intervention group was significantly decreased to 23.6% (P = 0.002) and 23.1% (P = 0.002), and the prevalence of pathogenic IPIs was reduced from 9.4% to 3.9% (P = 0.013) and 2.4% (P = 0.002), respectively. In contrast, no significant changes in the prevalence of IPIs were observed in the control group. The intervention group showed significant improvements in KAP scores, which were significantly higher than those in the control group. Conclusions MDA alone is not effective for controlling IPIs among the Karen people due to rapid reinfection related to behavioral factors and socioeconomic conditions. We demonstrated for the first time that integration of WASH education increased KAP scores and consequently significantly reduced IPI reinfection among the Karen hill tribe in northern Thailand. Graphical Abstract